THE ACCEPTANCE OF ALBANIA INTO THE NATIONS LEAGUE IN DECEMBER 17th, 1920 - Ahmetaj, Lavdosh (European Scientific Journal, ESJ, 2014)
The League of Nations came into existence after the end of the First World War. The task of the League of Nations was simply to ensure that war never arose again. However, after the turmoil which was caused by the Versailles Treaty, many have considered the League to bring stability to the world. America as a country embarked on the First World War in 1917, and the country as a whole and the president (Woodrow Wilson in particular) was horrified by the slaughter that had taken place in civilized part of the world. Thus, the only way to avoid the repetition of such disaster was to create an international body whose sole responsibility was to maintain world peace and resolve international disputes as and when they occurred. This is the task of the League of Nations of which Albania became a member. Therefore, the aim of this paper is to present the help and the policy followed by the members of this League for the acceptance of Albania.